Implementation of Islamic Religious Education Curriculum Based on Values to Form Students' Islamic Character - Juliani; Nabila; Nurmalasari; Nurul ‘Ala; Ramadhania Br Sitepu (Journal of Contemporary Islamic Primary Education, 2024)
Islamic Religious Education plays a vital role in shaping the Islamic character of students through the implementation of a value-based curriculum. This curriculum emphasizes not only cognitive aspects but also affective and psychomotor elements, enabling the internalization of Islamic values in students’ daily lives. This study aims to analyze the effectiveness of implementing a value-based IRE curriculum in shaping students' Islamic character. The method used is a literature review by analyzing various scientific journals related to the topic. The results of the study indicate that the implementation of the value-based IRE curriculum is effective in shaping students' Islamic character, with indicators such as improved noble morals, discipline, responsibility, and social awareness.